2013
DOI: 10.1007/s13353-013-0147-z
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis in podocin-associated hereditary nephrotic syndrome in Polish patients: founder effect in the Kashubian population

Abstract: Hereditary nephrotic syndrome is caused by mutations in a number of different genes, the most common being NPHS2. The aim of the study was to identify the spectrum of NPHS2 mutations in Polish patients with the disease. A total of 141 children with steroid-resistant nephrotic syndrome (SRNS) were enrolled in the study. Mutational analysis included the entire coding sequence and intron boundaries of the NPHS2 gene. Restriction fragment length polymorphism (RFLP) and TaqMan genotyping assay were applied to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…The c.1032delT variant has been previously reported as the most frequent pathogenic variant in NPHS2 in Poland (Kashubian region). 23 Both parents of patient 55 are of Polish extraction. In addition to these two patients, a further 30 had variants without a previous disease association in the following genes: ACTN4 (1 patient), COL4A3 (2), COL4A4 (1), COL4A5 (10), INF2 (2), LAMB2 (2), NPHS1 (5), NPHS2 (2), SMARCAL1 (1), TRPC6 (1) and WT1 (3).…”
Section: Resultsmentioning
confidence: 99%
“…The c.1032delT variant has been previously reported as the most frequent pathogenic variant in NPHS2 in Poland (Kashubian region). 23 Both parents of patient 55 are of Polish extraction. In addition to these two patients, a further 30 had variants without a previous disease association in the following genes: ACTN4 (1 patient), COL4A3 (2), COL4A4 (1), COL4A5 (10), INF2 (2), LAMB2 (2), NPHS1 (5), NPHS2 (2), SMARCAL1 (1), TRPC6 (1) and WT1 (3).…”
Section: Resultsmentioning
confidence: 99%
“…Also, no m.3243A > G (rs199474657) in MT-TL1 , previously linked to kidney failure, FSGS and SRNS [ 50 , 51 ], was found in this study. Next, we analyzed NPHS2 mutations that have been assigned to 30% of steroid resistant forms of NS in children, especially R138Q (rs574315342) and R229Q (rs1057516414), commonly attributed to SRNS in East Europeans [ 2 , 4 , 52 ]. We spotted no R138Q, whereas 6 patients (3 SR, 2 PSS, 1 SD) and 5 controls had heterozygous R229Q.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Lipska et al explored the spectrum of NPHS2 gene mutations causing steroid-resistant nephrotic syndrome in Polish patients and reported that the carriers of the c.1032delT allele were exclusively found in the Pomeranian (Kashubian) region, suggesting a founder effect origin [ 42 ]. Studies of Chmara et al in the population of patients with hypercholesterolaemia suggested that the (c.662A>G variant in the LDLR gene is frequent in this population) [ 23 , 38 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%